Convenient procedures for the biosynthesis, isolation, and isotope labeling of cytochalasins. - Zabel, R A (1979)
Efforts to improve small-scale yields of useful cytochalasins by fermentation resulted in selection of an enriched aflatoxin medium which increased yields by fivefold over those reported in the literature. With Helminthosporium dematoideum and Zygosporium masonii in stationary culture for 3 weeks, cytochalasins B and D were obtained in quantities approaching 700 and 500 mg/liter, respectively. It appears that the critical component in this growth medium is factors associated with whole wheat. By using these procedures, coupled with improvements in isolation, supplementation with two radioactive phenylalanine species readily produced [14C]- or [3H]cytochalasin B. Oxidation of carrier-free radioactive cytochalasin B to cytochasasin A readily provided this labeled congener as well. The isotopic ocnversion of precursor to crystalline products that met analytical criteria ranged from 2 to 4% of the administered radioactivity.